KEMAMPUAN LITERASI MATEMATIS SISWA MELALUI MODEL LEARNING CYCLE BERBANTUAN GOOGLE CLASSROOM - Ari Septian; Guntur Maulana Muhammad; Ismi Zakiyatu Rahmah (Jurnal Padegogik, 2022)
The purpose of the study was to determine students' mathematical literacy skills in working on problems through the learning cycle model. The type of research used is descriptive research using a qualitative approach. The subjects in this study were 6 students of class XI MIPA MA Al-Ma'arif for the 2020/2021 academic year. Data collection techniques used are tests and questionnaires. The instruments used are students' mathematical literacy ability tests, google classroom questionnaires. The data analysis technique used the Miles and Huberman model, namely, data reduction, data presentation, and drawing conclusions. The results showed that 1) the mathematical literacy ability in the very good category was 33%; 2) mathematical literacy ability in good category by 33%; and 3) mathematical literacy ability in the less category of 33%. In conclusion, students' abilities related to working on items with indicators of mathematical literacy skills combined with the learning cycle model are on average good. The implication, interest and motivation to learn as well as the ability to use high technology